Breast MRI screening for average‐risk women: A monte carlo simulation cost–benefit analysis. Issue 7 (11th January 2019) - Mango, Victoria L.; Goel, Akshay; Mema, Eralda; Kwak, Ellie; Ha, Richard
Abstract : Background: Screening high‐risk women for breast cancer with MRI is cost‐effective, with increasing cost‐effectiveness paralleling increasing risk. However, for average‐risk women cost is considered a major limitation to mass screening with MRI. Purpose: To perform a cost–benefit analysis of a simulated breast cancer screening program for average‐risk women comparing MRI with mammography. Study Type: Population simulation study. Population/Subjects: Five million (M) hypothetical women undergoing breast cancer screening. Field Strength/Sequence: Simulation based primarily on Kuhl et al 8 study utilizing 1.5T MRI with an axial bilateral 2D multisection gradient‐echo dynamic series (repetition time / echo time 250/4.6 msec; flip angle, 90°) with a full 512 × 512 acquisition matrix and a sensitivity encoding factor of two, performed prior to and four times after bolus injection of 0.1 mmol of gadobutrol per kg of body weight (Gadovist; Bayer, Germany). An axial T2 ‐weighted fast spin‐echo sequence with identical anatomic parameters was also included. Assessment: A Monte Carlo simulation utilizing Medicare reimbursement rates to calculate input variable costs was developed to compare 5M women undergoing breast cancer screening with either triennial MRI or annual mammography, 2.5M in each group, over 30 years. Statistical Tests: Expected recall rates, BI‐RADS 3, BI‐RADS 4/5 cases and cancer detection rates were determined from published literature with calculated aggregate costs including resultant diagnostic/follow‐up imaging and biopsies. Results: Baseline screening of 2.5M women with breast MRI cost $1.6 billion (B), 3× higher than baseline mammography screening ($0.54B). With subsequent screening, MRI screening is more cost‐effective than mammography screening in 24 years ($13.02B vs. $13.03B). MRI screening program costs are largely driven by cost per MRI exam ($549.71). A second simulation model was performed based on MRI Medicare reimbursement trends using a lower MRI cost ($400). This yielded a cost‐effective benefit compared to mammography screening in less than 6 years ($3.41B vs. $3.65B), with over a 22% cost reduction relative to mammography screening in 12 years and reaching a 38% reduction in 30 years. Data Conclusion: Despite higher initial cost of a breast MRI screening program for average‐risk women, there is ultimately a cost savings over time compared with mammography. This estimate is conservative given cost–benefit of additional/earlier breast cancers detected by breast MRI were not accounted for. Level of Evidence: 3 Technical Efficacy Stage: 6 J. Magn. Reson. Imaging 2019.